Medical education through an invasion: insights from an elective programme for Ukrainian medical students at the University of Cambridge - Hodkinson, Joy; Lillicrap, Mark; Wilkinson, Paul; Bevan, Stephen; Shenheliia, Tamari; Chupina, Vilena; Fuld, Jonathan (Frontiers in Medicine, 2023)
Medical Students in Ukraine have faced extraordinary disruption to their clinical studies with both the COVID-19 pandemic and subsequent Russian military invasion forcing a majority of their learning to be conducted remotely. Over the summer of 2022, the University of Cambridge School of Clinical Medicine hosted twenty medical students from Kharkiv National Medical University for a seven-week intensive clinical elective programme. The aim was to provide an immersive clinical placement that would help students to attain the necessary knowledge and experience to become competent and confident practising doctors. This perspective piece aims to support the development of future equivalent exchanges through outlining the placement's context, its planning and implementation, evidence of placement impact, and finally reflections and learning points.